A Correlational Literature Review On Urvi and Bahavi Marma with Special Reference to Urvi Avedhya Sira: Life Sciences -Ayureveda - B. Dole, Vidya; Deshpande, Y. N. (International Journal of Life Science and Pharma Research, 2023)
Ayurveda’s physiological and anatomical concepts are among the unique features of Ayurveda therapeutics. The concepts of Sharira, such as Sira (Vein), Snayu (Ligaments), Srotas (Channels), Peshi (Muscles), Marma (Vital points), etc., and their relation with Sharira Dosha, can help in understanding pathophysiology given Ayurveda. While studying these, it is essential to understand their exact structure and location. Marma’s are the vital spots in the human body means any injury to that point can lead to symptoms like pain, blood loss, deformity, and death. Concepts like Marma and Sira Sharir are very important and have many contributions while treating patients. Hence, knowing this particular part’s exact structure and location is essential in treating related diseases. So, this review study aims to determine the exact structure of Urvi and Bahavi Marma w.s.r Urvi Sira. The objectives of this study are to determine the exact location and structure and to evaluate the correlation between Urvi and Bahavi Marma w.s.r Urvi Sira with the help of all available relevant literature from Ayurvedic Samhita, modern science, and journals.